Compare the Quality of Administration in Public and Punjab Education Foundation Funded Schools at Secondary Level - Sabir Hussain,; Dr. Masood Ahmad,; Dr. Ijaz Hussain,; Aqila Hafeez,; Dr. Rukhsana Sardar,; Fakhar-Ul-Zaman, (Al-Qanṭara, 2024)
Effective school administration fosters a supportive learning environment, promotes quality teaching, and ensures efficient resource utilization to optimize student outcomes. Public and PEF secondary schools in Punjab emphasize quality administration, fostering a conducive learning environment, supporting qualified teachers, and optimizing resource utilization to enhance student outcomes. The said research was a cross-sectional survey approach and quantitative. Data was collected from 300 teachers in three districts of Punjab province. Data was collected through a 5-point Likert type scale and analyzed through an independent samples t-test. It was found that teachers in both public and PEF-funded schools generally have positive perceptions of school administration. However, teachers in government schools tend to have more positive perceptions than teachers in PEF-funded schools. It found that government schools may be more effective in carrying out vital administrative functions and processes, supporting teachers’ professional development, creating a positive and supportive work environment, and fostering a culture of continuous improvement and innovation. It is suggested that PEF schools should benchmark government schools’ administrative practices to improve teacher perceptions and enhance overall school effectiveness. Keywords: Quality of Administration, PEF schools, Public secondary schools, Administration Effectiveness.